Deviation in Song Lyrics: A Study How Songwriters Use Deviation to Creative Emotional Resonance, Tell Stories or Convey Messages - Khan, Imran Ali; Ur Rehman, Zohaib; Amir, Fizza (2024)
This study conducts a discourse analysis of song lyrics to examine the linguistic, discourse, and poetic devices used to create meaning and shape listener interpretation. Analyzing 15 song lyrics, the research reveals patterns of deviation in language use, highlighting how songwriters challenge dominant discourses and create new meanings. The findings provide insights into how language and music intersect and demonstrate how song lyrics can be used to explore complex social and cultural issues. The study's results contribute to our understanding of the role of language and music in shaping our experiences and perceptions, with implications for music therapy, education, and cultural studies. This study is delimited to a qualitative analysis of song lyrics and does not include other music or artistic expression forms. The study focuses specifically on the linguistic, discourse and poetic devices used in song lyrics and does not examine other aspects of music, such as melody, harmony, or rhythm. The study is also limited to analyzing 15 song lyrics and does not claim to represent all song lyrics or genres. The study's findings are also based on critical discourse analysis and may not be generalizable to other research methods or approaches. The study's focus on deviation in language use also delimits the study to examine how songwriters challenge dominant discourses and does not explore other ways language and music intersect.